Derivational and Inflectional Morphemes in Pak-Pak Language - Agustina Situmorang; Tina Mariany Arifin (State University of Medan, 2012)
The objectives of this study are to find out the derivational and inflectional morphemes in Pak-Pak language in terms of word class, form and meaning and to find out the similarities and differences of the derivational and inflectional morphemes in English and Pak-Pak languages. This study was conducted by using descriptive qualitative. The data were obtained by applying a documentary techique. The findings showed that there were some similarities and differences of derivational and inflectional morphemes in English and Pak-Pak languages. The similarities are both languages are formed by prefix and suffix. Both languages have similar, they can attached by noun, verb, adjective and adverb. They also have differences, the formation of derivational in English is only formed by prefix and suffix. While in Pak-Pak languages are forming by prefix, suffix, infix, and confix. Inflectional in English is only formed by suffix. While in Pak-Pak languages, they are prefix, suffix, infix, and confix. In conclusion, there are similarities and differences of derivational and inflectional morphemes between English and Pak-Pak languages. Key Words: Derivational, inflectional morphemes